Nutritional profile of household dogs and cats in São Luís – Maranhão - Costa, Sércio; Souza, Daniel; Souza, Mikaelle; Correia, Kamylla; Almeida, Leandra; Sousa, Leandro; Santos, Victoria; Lima, Larissa (Pubvet, 2021)
The objective of the study was to build the profile of the nutritional management of pets in the city of São Luís - Maranhão through the application of a questionnaire composed of objective and discursive questions in 107 people living in 38 neighborhoods in the city. The degree of knowledge about animal feeding, habits in the supply of food to their pets and socioeconomic level were evaluated. The main food offered to the animals was dry commercial food, with an average monthly expenditure of 148 reais on nutritional assistance, however there are still tutors who give human food daily without knowledge of the safety and quality of nutrients in the food offered. The most cited source of information was the routine veterinary consultation and the internet. Most tutors report complying with the minimum nutritional requirements, but a variability of criteria was noted. The tutors demonstrated knowledge related to basic nutritional management and a greater technical dissemination on this topic is recommended, since it is vital for maintaining the health of dogs and cats.